2007
DOI: 10.1021/pr060549i
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis and MALDI Imaging of Formalin-Fixed, Paraffin-Embedded Tissue Sections

Abstract: Formalin fixation, generally followed by paraffin embedding, is the standard and well-established processing method employed by pathologist. This treatment conserves and stabilizes biopsy samples for years. Analysis of FFPE tissues from biopsy libraries has been, so far, a challenge for proteomics biomarker studies. Herein, we present two methods for the direct analysis of formalin-fixed, paraffinembedded (FFPE) tissues by MALDI-MS. The first is based on the use of a reactive matrix, 2,4-dinitrophenylhydrazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
258
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(268 citation statements)
references
References 34 publications
5
258
0
2
Order By: Relevance
“…A decade of developments in instrumentation and chemistry has been required to achieve optimal extraction, detection, and spatial resolution when mapping compounds at the tissue level (Franck et al 2009a, b;Lemaire et al 2006a, b;2007a;van Remoortere et al 2010). These developments, combined with using the appropriate data-processing tools, gave rise to the discovery of biomarkers for diverse pathologies (Bonnel et al 2011;Djidja et al 2010;McCombie et al 2005;Stauber et al 2008), of which cancer is the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…A decade of developments in instrumentation and chemistry has been required to achieve optimal extraction, detection, and spatial resolution when mapping compounds at the tissue level (Franck et al 2009a, b;Lemaire et al 2006a, b;2007a;van Remoortere et al 2010). These developments, combined with using the appropriate data-processing tools, gave rise to the discovery of biomarkers for diverse pathologies (Bonnel et al 2011;Djidja et al 2010;McCombie et al 2005;Stauber et al 2008), of which cancer is the most studied.…”
Section: Introductionmentioning
confidence: 99%
“…Lemaire et al [13] showed that a combination of in situ extraction with in situ micro digestion performed on FFPE tissues allows the identification of proteins by nanoLC-nanoESI and MALDI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Schwartz et al [12] obtained good results in the prognosis of brain tumor patient by MALDI-IMS carried out on fresh frozen tissues. Furthermore, Lemaire et al [13] showed that a combination of in situ extraction with in situ microdigestion performed on FFPE tissues allows the identification of proteins by nanoLC-nanoESI and MALDI imaging.…”
Section: Introductionmentioning
confidence: 99%
“…This work demonstrates significant improvements in the sensitivity, the number of observed analytes, the detection of larger proteins, and importantly allows unambiguous MS/MS identification directly from the tissue. Enzymatic digestion prior to IMS has also been applied to the analysis of formalin-fixed paraffin-embedded (FFPE) tissue [11]. FFPE is the predominant method for tissue preservation and storage; however, the procedure cross-links proteins, preventing classical proteomic analysis.…”
Section: Applicationsmentioning
confidence: 99%